Absent Felicity. Issue 3 (1st September 2020) - Sanders, Andrew
Abstract: 'Happiness', as we now commonly understand the term, is not something we should expect to meet in Shakespeare's work. When he employs alternative words – such as 'felicity, 'merry' or 'blessed' – he rarely seeks to convey what latter-day readers might assume to be the concept of 'happiness' that we accept as an agreeable state of mind. Shakespeare's 'happy' seems to apply to circumstances rather than to a state of mind. His characters often appear to be luckier in their happiness rather than actual achievers of happiness. The idea that the 'pursuit of happiness' is an essential part of the definition of the human condition (as in the founding documents of the American Revolution) may well owe far more to John Milton's use of the words 'happy' and 'happiness' and the common acceptance of 'happiness' as a socially and politically desirable condition.